Pengaruh Kinerja Pegawai Terhadap Kualitas Pelayanan Di Perusahaan Daerah Air Minum Kota Tomohon - Supit, Tissy J P (JURNAL ILMIAH SOCIETY, 2015)
Municipal Waterworks in Tomohon City is a state-owned enterprise that aim to provide service to the community, especially in Tomohon city. In the process Municipal Waterworks Tomohon city still has many fault become an obstacle  the performance of employees  have an impact on the quality of the service to customer . The aim of this study is to The Influence of  Performance  Employees on the Quality of Service in the Municipal Waterworks (PDAM) in Tomohon City.The methodology used was quantitative research. This research Municipal Waterworks used in Tomohon city . The population is all employees of PDAM Tomohon and all customers. The total sample of 145 respondents. Data analysis are validity and reliability, the classic assumption test and followed by multiple linear regression analysis. Results of this study found that a positive or significant influence on the performance of employees consisting a few of variables of quantity, quality, time, cost, and place and space to service quality in Municipal Waterworks  ( PDAM ) in Tomohon city. Simultaneously has a different effect between employee performance to service quality in Municipal Waterworks   (PDAM) in Tomohon city. It is suggested for  Municipal Waterworks   ( PDAM) in Tomohon City should increase the performance of employees consisting of quantity, quality, time, cost, and place and space so that the quality of service has increased.